Criminalization of Serial Marriage Perpetrators in Criminal Law in Indonesia - Suriansa Suriansa; Nur Insani; Apriyanto Nusa (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
This study aims to analyze the legal regulation of serial marriage in the Indonesian legal system and examine the urgency of criminalization of serial marriage perpetrators from the perspective of criminal law. The research method used is normative juridical with legislative, conceptual, and case approaches, through literature studies on primary, secondary, and tertiary legal materials. The results of the study show that the regulation of nikah siri in Indonesian law has not provided optimal legal certainty and protection, especially for women and children, even though it has been regulated in Law Number 1 of 1974 concerning Marriage jo. Law Number 16 of 2019 concerning Amendments to the Marriage Law, due to weak enforcement and the absence of strict sanctions for violations of marriage registration. On the other hand, the criminalization of serial marriage in criminal law has not been appropriately applied because it contradicts the basic principles of criminal law such as the principle of legality in the Criminal Code and has the potential to clash with religious freedom in the 1945 Constitution of the Republic of Indonesia. Therefore, a more effective approach is through strengthening the administrative system, increasing public legal awareness, and more optimal legal protection for women and children